2018 IEEE 15th International Symposium on Biomedical Imaging (ISBI 2018) 2018
DOI: 10.1109/isbi.2018.8363854
|View full text |Cite
|
Sign up to set email alerts
|

Transfer learning for diagnosis of congenital abnormalities of the kidney and urinary tract in children based on ultrasound imaging data

Abstract: Classification of ultrasound (US) kidney images for diagnosis of congenital abnormalities of the kidney and urinary tract (CAKUT) in children is a challenging task. It is desirable to improve existing pattern classification models that are built upon conventional image features. In this study, we propose a transfer learning-based method to extract imaging features from US kidney images in order to improve the CAKUT diagnosis in children. Particularly, a pre-trained deep learning model (imagenet-caffe-alex) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In particular, anatomic characteristics derived from US imaging, such as renal elasticity, are associated with kidney function (Meola et al, 2016) and lower renal parenchymal area measured on US images is associated with increased risk of end-stage renal disease (ESRD) in boys with posterior urethral valves (Pulido et al, 2014). Imaging features computed from US data using deep convolutional neural networks (CNNs) improved the classification of children with congenital abnormalities of the kidney and urinary tract (CAKUT) and controls (Zheng et al, 2019;Zheng et al, 2018a). The computation of these anatomic measures typically involves manual or semi-automatic segmentation of kidneys in US images, which increases inter-operator variability, reduces reliability, and limits utility in clinical medicine.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, anatomic characteristics derived from US imaging, such as renal elasticity, are associated with kidney function (Meola et al, 2016) and lower renal parenchymal area measured on US images is associated with increased risk of end-stage renal disease (ESRD) in boys with posterior urethral valves (Pulido et al, 2014). Imaging features computed from US data using deep convolutional neural networks (CNNs) improved the classification of children with congenital abnormalities of the kidney and urinary tract (CAKUT) and controls (Zheng et al, 2019;Zheng et al, 2018a). The computation of these anatomic measures typically involves manual or semi-automatic segmentation of kidneys in US images, which increases inter-operator variability, reduces reliability, and limits utility in clinical medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we note that Deep Learning has also been applied in non-reconstruction tasks to ultrasound, including classification [60], [61] and segmentation [62].…”
Section: Deep Learningmentioning
confidence: 99%
“…The AUC for classifiers built on the combination features were 0.92, 0.88, and 0.92 for discriminating the left, right, and bilateral abnormal kidney scans from controls with classification rates of 84%, 81%, and 87%; specificity of 84%, 74%, and 88%; and sensitivity of 85%, 88%, and 86%, respectively. It is suggested that the combination of transfer learning features and conventional imaging features yielded the best classification performance for distinguishing CAKUT patients from normal controls based on their ultrasound kidney images [49,50].…”
Section: Imaging Diagnosismentioning
confidence: 99%